Days of Work over a Half Century: The Rise of the Four-Day Week - Daniel S. Hamermesh; Jeff E. Biddle (Institute of Labor Economics (IZA), 2022)
We examine work patterns in the U.S. from 1973-2018, with the novel focus on days per week, using intermittent CPS samples and one ATUS sample. Among full-time workers the incidence of four-day work tripled, with 8 million additional four-day workers. Similar growth occurred in the Netherlands, Germany, and South Korea. The rise was not due to changes in demographics or industrial structure. Such schedules are more common among less educated, younger, and white non-Hispanic workers, men, natives, and people with young children; police and firefighters, health-care, and restaurant workers. Based on an equilibrium model, we show that they result more from workers' preferences and/or daily fixed costs of working than production costs. We verify the implication that the wage penalty for four-day work is greater where such work is more prevalent, and we show that the penalty has diminished over time.
Keywords: J11; J22; 330; days/week; decomposition; labor supply; wage penalties